Risk evaluation and analysis of a gas tank explosion based on a vapor cloud explosion model: A case study. (July 2019) - Zhang, Qingtao; Zhou, Gang; Hu, Yingying; Wang, Shicong; Sun, Biao; Yin, Wenjing; Guo, Fengshou
Abstract: A gas tank is an important storage facility in chemical enterprises. When an explosion occurs, it can easily cause mass injury and death. This paper takes a 50, 000 m 3 gas tank as an example to analyze the consequences of an accident. First, a TNT-equivalent explosion model, quantitative risk analysis and FLACS software are used to quantitatively analyze the explosion consequences. The range of casualties caused by the vapor cloud explosion is obtained. The simulation results are then compared with the actual damage range of a gas tank explosion, and the accuracy of the simulation results is verified. Next, the personal and social risks of a gas tank are identified according to China's national standards, and it is concluded that the individual risk can be tolerated, the social risk is within the tolerable range and its area has been reduced as far as possible, and it is necessary to minimize the overall risk as much as possible. Finally, a qualitative analysis of the gas tank explosion accident is carried out and the causes of the accident are analyzed. These analyses can be used to guide practices and effectively prevent the occurrence of similar accidents. Graphical abstract: Unlabelled Image Highlights: Obtain the range of casualties caused by the vapor cloud explosion. The actual damage range is verified by simulation results for the first time. Personal and social risks of a gas tank explosion are identified. Guide practices and effectively prevent the occurrence of similar accidents.